Amyloid β Oligomers Increase ER-Mitochondria Ca2+ Cross Talk in Young Hippocampal Neurons and Exacerbate Aging-Induced Intracellular Ca2+ Remodeling - Calvo-Rodriguez, Maria; Hernando-Perez, Elena; Nuñez, Lucia; Villalobos, Carlos (Frontiers in Cellular Neuroscience, 2019)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder and strongly associated to aging. AD has been related to excess of neurotoxic oligomers of amyloid β peptide (Aβo), loss of intracellular Ca2+ homeostasis and mitochondrial damage. However, the intimate mechanisms underlying the pathology remain obscure. We have reported recently that long-term cultures of rat hippocampal neurons resembling aging neurons are prone to damage induced by Aβo while short-term cultured cells resembling young neurons are not. In addition, we have also shown that aging neurons display critical changes in intracellular Ca2+ homeostasis including increased Ca2+ store content and Ca2+ transfer from the endoplasmic reticulum (ER) to mitochondria. Aging also promotes the partial loss of store-operated Ca2+ entry (SOCE), a Ca2+ entry pathway involved in memory storage. Here we have addressed whether Aβo treatment influences differentially intracellular Ca2+ remodeling in young and aged neurons. We found that Aβo exacerbate the remodeling of intracellular Ca2+ induced by aging. Specifically, Aβo exacerbate the loss of SOCE observed in aged neurons. Aβo also exacerbate the increased resting cytosolic Ca2+ concentration, Ca2+ store content and Ca2+ release as well as increased expression of the mitochondrial Ca2+ uniporter (MCU) observed in aging neurons. In contrast, Aβo elicit none of these effects in young neurons. Surprisingly, we found that Aβo increased the Ca2+ transfer from ER to mitochondria in young neurons without having detrimental effects. In striking contrast, Aβo suppressed this transfer in aged neurons which correlated with apoptosis. These results suggest that modulation of ER – mitochondria coupling in hippocampal neurons may be a novel physiological role of Aβo. However, excess of Aβo in the face of the remodeling of intracellular Ca2+ concentration associated to aging may lead to loss of ER – mitochondrial coupling and AD.